Energy Consumption Patterns and Residential Carbon Footprint in Turkey - Kaya, Mustafa (Journal of Environment, 2025)
Purpose: The purpose of this article was to analyze energy consumption patterns and residential carbon footprint in Turkey. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Turkey, rapid urban growth and aging infrastructure have led to high residential carbon emissions primarily driven by fossil fuels, with households emitting around 4.8 tonnes of CO₂ annually. Recent government initiatives in energy efficiency and renewable integration have begun to moderate these trends, although challenges remain for sustainable urban development. Unique Contribution to Theory, Practice and Policy: Ecological modernization theory (EMT), social practice theory & diffusion of innovations theory may be used to anchor future studies on the analyze energy consumption patterns and residential carbon footprint in Turkey. Practitioners should leverage state-of-the-art monitoring technologies such as smart meters and IoT devices to capture detailed data on residential energy use. Policymakers must design incentive schemes, such as tax rebates and subsidies, to encourage the adoption of renewable energy and energy-efficient retrofits in residential areas.